High Throughput Screening of Potential Neuroprotective Compounds Using a Herpes-Induced Brain Model of Sporadic Alzheimer's Disease - Silveira, Isabella A. (Tufts Archival Research Center, 2021)
Here, we describe a screening of a number of notable neuroprotective compounds with links to neurodegenerative disorders using a herpes-induced AD brain model previously published by the Kaplan Lab. We report successful reductions in Aβ plaque-like formation in five compounds: metformin, resveratrol, curcumin, green tea catechins, and citicoline. Impact of the compounds on neuronal function and expression of various genes were assessed with varying results and success. Preliminary results suggest potential viability of the compounds as AD therapeutics; however, further study is needed to elucidate the exact mechanisms by which these compounds may be alleviating the AD phenotype.; Advisor: David Kaplan, Ph.D.